2010
DOI: 10.1002/ajpa.21440
|View full text |Cite
|
Sign up to set email alerts
|

The big and small of it: How body size evolves

Abstract: Body size is a biological variable of fundamental importance and plays a central role in analyses of life history, sexual dimorphism, allometry, and natural and sexual selection. Yet, there remains a sizeable gulf in our understanding that lies between what we hypothesize influences change in size, from the point of view of ultimate causation, and what we know about how shifts in body size are regulated from a proximate perspective. I seek here to tie these two perspectives together, and specifically to argue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 211 publications
(202 reference statements)
1
11
0
Order By: Relevance
“…In addition, Ringsby et al (2015) showed, in house sparrows, that selection for increased body size led to a reduction in mean telomere length. The existence of a negative body size-telomere length relationship is consistent with the pattern often observed within populations that larger individuals tend to live less long (Bartke, 2012;Bernstein, 2010;Miller, Harper, Galecki, & Burke, 2002), given that shorter telomeres at the end of development are associated with reduced longevity (Boonekamp, Mulder, Salomons, Dijkstra, & Verhulst, 2014;Heidinger et al, 2012).…”
supporting
confidence: 86%
“…In addition, Ringsby et al (2015) showed, in house sparrows, that selection for increased body size led to a reduction in mean telomere length. The existence of a negative body size-telomere length relationship is consistent with the pattern often observed within populations that larger individuals tend to live less long (Bartke, 2012;Bernstein, 2010;Miller, Harper, Galecki, & Burke, 2002), given that shorter telomeres at the end of development are associated with reduced longevity (Boonekamp, Mulder, Salomons, Dijkstra, & Verhulst, 2014;Heidinger et al, 2012).…”
supporting
confidence: 86%
“…Size variation within species is known to be highly polygenic and involve multiple physiological systems 3840 and genes, including GH, IGF1, leptin, and ubx 4144 . While the Q/R variation at position 156 of the MC4R does not have a monogenic effect on size determination, given the existence of the Q156 allele of the receptor in mammals and the existence of the R156 allele in the larger odontocetes, we nonetheless observed that EC 50 values for the 17 non-redundant cetacean MC4Rs were significantly correlated with both body length and body weight (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Size is an obvious axis of phenotypic variation, and considerable attention has been paid to evolutionary diversification of size (e.g., Cope's rule, Bergmann's rule, Rensch's rule; Bernstein 2010). Larger individuals appear to be generally fitter, through both increased survival and mating success (Kingsolver and Pfennig 2004).…”
Section: Discussionmentioning
confidence: 99%